Carcass and meat quality of red-winged tinamou (Rhynchotus rufescens) selected for muscle growth - Martins, Eduardo Henrique [UNESP] (2023)
The aim of the present study was to evaluate the efficiency of selection for body growth and its association with carcass and meat quality traits in the red-winged tinamou. Two experimental groups were selected based on the selection index: selection group with a higher index (TinamouS) and commercial group with a lower index (TinamouC). Weight at 180 days and slaughter weight were significantly higher (p < 0.05) in the TinamouS group, as were hot carcass weight, skinless breast weight, wing weight, and thigh and drumstick weight. The meat quality traits or sensory attributes did not differ significantly (p > 0.05) between groups. A significant positive correlation (0.59; p < 0.05) was found between shear force and chewability and a significant negative correlation (− 0.59; p < 0.05) between aroma intensity and strange aroma. The present study suggests that the selection index promotes greater body growth and preserves meat quality and sensory traits in red-winged tinamou.